Monetary policy surprises and their transmission through term premia and expected interest rates - Iryna Kaminska; Haroon Mumtaz; Roman éSustek (Queen Mary University of London, School of Economics and Finance, 2020)
Monetary policy moves the yield curve. How much is due to expected interest rates vs. term premia? And does it matter for macroeconomic outcomes? Using an affine term structure model, we shed new light on these questions. Estimation is subject to restrictions addressing an estimation bias in expected interest rates obtained by previous studies. Highfrequency yield curve decomposition around FOMC announcements into term premia and expected interest rates then provides instruments for a local projection model. The effects of interest rate expectations and term premia are found equally important for the transmission mechanism and broadly consistent with macroeconomic theory.
Keywords: E43; E52; E58; G12; C58; 330; High-frequency data; monetary policy transmission mechanism; restricted affine term structure models; yield curve decomposition; local projection method; Bayesian estimation